a Edukasi hiperkolesterolemia untuk pencegahan penyakit kardiovaskular pada Muslimat NWDI NTB - Intan Nefia; Ero Ari Angga; Linda Mahardhika; Arief Rahman; Andi Nizam Harahap; Zahrah Firdaus; Yosilia Nursakina; Hartini Haritani; Kayisa Rahmania Salim; Najjiya Azzahra; Sitti Rohmi Djalilah (Universitas Hamzanwadi, 2026)
Hypercholesterolemia is one of the risk factors for cardiovascular disease that needs to be controlled through the implementation of a healthy lifestyle and regular health screening. Limited public knowledge regarding risk factors, dietary patterns, genetic factors, and preventive measures for hypercholesterolemia highlights the need for community-based health education. This community service activity aimed to provide education on hypercholesterolemia and cardiovascular disease prevention to members of Nahdlatul Wathan Diniyah Islamiyah (NWDI) Muslimat in West Nusa Tenggara Province. The activity was conducted on February 22, 2026, at the North Lombok Regent’s Hall and involved 62 female participants aged 19–70 years. The activities employed interactive lectures, discussions, and question-and-answer sessions. Evaluation was conducted observationally by assessing participant participation, engagement in discussions, and responses to the educational materials. The results showed that participants attended the activity from beginning to end, actively asked questions and shared experiences, and provided positive responses to the materials presented. Participants’ questions mainly concerned dietary patterns, foods that should be limited or recommended, genetic factors, and the recommended frequency of cholesterol screening. Participants also considered the materials easy to understand, relevant, and useful for application in daily life. These findings indicate that community-based health education can serve as a relevant promotive approach for disseminating information on hypercholesterolemia and cardiovascular disease prevention. Further evaluation using quantitative instruments is needed to objectively measure changes in participants’ knowledge and health-related behaviors.